It Was a Dark and Stormy Night: Chaim Kruger as an Author of Serialized Novels in the Keneder Adler, 1927–1933 - Robinson, Ira (Canadian Jewish Studies / Études juives canadiennes, 2025)
Chaim Kruger (1877–1933) was born in Lithuania, educated in Lithuanian yeshivas, and became a personality of some importance in the Montreal Jewish community after his emigration to Canada in 1907. He was a rabbi, a rosh yeshiva (teacher of Talmud), a shokhet (kosher slaughterer), and, not least, a mainstay on the journalistic staff of Montreal’s Yiddish newspaper, Der Keneder Adler, from 1921 to 1933. At the Keneder Adler, he contributed to nearly every section of the newspaper. Kruger translated into Yiddish the wire service reports of items of national and international interest for the front page. He wrote thousands of articles under his own name as well as several pseudonyms on a wide range of subjects including extended series of articles on Judaic studies, Canada–US relations, economics, and ecology on the editorial and op-ed pages. He edited the newspaper’s weekly children’s column as well as its daily advice column. Not least, from 1927 to 1933, Chaim Kruger published no fewer than ten serial novels in the Keneder Adler under the pseudonym “Hyman Zinman.” None of them was ever published in book form. This article will briefly survey all of Kruger’s serialized novels, and examine one, Der Froyen yeger (The Stalker of Women), in greater detail. It will attempt to situate Kruger’s novelistic oeuvre in the context of the publication of scores of such serialized novels in the North American Yiddish press in the early twentieth century as well as in the context of attitudes toward popular Yiddish literature (shund) during that period.